Supply Chain Performance Measurement at PT. Perkebunan Nusantara XIV Camming Sugar Factory in Bone District - Saleh, Anis; Ahmad, Arfandi; Herdianzah, Yan; Lantara, Dirgahayu; Saputra, Nur Ihwan; Dahlan, Muhammad (Universitas Atma Jaya Yogyakarta, 2023)
PTPN XIV (PERSERO) of Camming Sugar Factory in Bone Regency Measuring work results in the company is one of the company's performance evaluation tasks, namely to find out if the results achieved are good enough or still need improvement. The characteristic of a weak result is the fact that the company's goal is not achieved in the desired way. The objective of this study is to identify the KPIs and measure the performance indicators at the Bone Regency of PTPN Camming Sugar Factory. Key Performance Indicator (KPI), Lean Supply Chain Management (LSCM), and Analytic Hierarchy Process (AHP) methods are used in this study. The results of this study provide 11 Lean metrics that align with business conditions. Once the indicators are obtained, the KPI weighting is carried out using the Analytical Hierarchy Process (AHP), prioritizing the performance criteria of the production and supply departments. KPIs that have a significant impact on a company's supply chain performance. This is reflected in the highest order of weight in three KPIs, namely production department performance criteria, employee productivity attributes (0.573) and delivery department criteria, on-time loading (0. 85), and delivery (0.372) attributes. with a weight percentage of 19.1, 16.20% and 12. 2%. The KPIs in the lowest weight category are collection (0.120) and delivery (0.116) with a weight percentage of .01% and 3.87%.